Perempuan Dalam Tantangan Modernitas : Women In The Challenges Of Modernity - Nanik Mahmuda (An-Nisa’ Journal of Gender Studies, 2015)
Whether we admit it or not, human life in the modern world is undergoing rapid change, especially for women. However, these changes have not completely transformed the lives of women, who continue to suffer from discrimination and social constructs that lead to dehumanization. The freedom that women have gained in the modern era has turned out to be a new problem for women, and even a shackle that is very difficult to break free from. The freedom of women in question tends to be steeped in consumerism and materialistic values that alter patterns of thinking and modern culture, moving away from religious values and prevailing norms. Yet Islam has regulated women's freedom in such a way that it does not undermine ethical order and moral values. Diakui atau tidak kehidupan manusia dalam memasuki dunia modernitas mengalami perubahan yang sangat cepat, terutama bagi perempuan. Namun perubahan tersebut tidak secara totalitas mengubah kehidupan perempuan yang selama ini tidak terlepas dari diskriminasi dan konstruk sosial yang mengarah pada dehumanisasi. Kebebasan perempuan yang mendapatkan tempat di era modernitas ternyata menjadi persoalan baru bagi perempuan, bahkan belenggu yang sangat sulit di lepaskan. Kebebasan perempuan yang dimaksud cenderung kental dengan kehidupan konsumerisme dan hal-hal yang bersifat materialistik yang mengubah pola berpikir dan budaya modern yang jauh dari nilai-nilai agama dan normanorma yang berlaku. Padahal Islam telah mengatur kebebasan perempuan dalam berperan sedemikian rupa tanpa merusak tatanan etika dan nilainilai moral.